THE VALUE AND QUALITY OF WATER - R. N. Muminova; Сh. Ergasheva (Galaxy International Interdisciplinary Research Journal, 2023)
The main role of water in the biosphere is that it is a medium and a source of hydrogen for life processes. It can be argued that all living things consist of water and organic substances. The article highlights the great importance of water for life on earth and the quality of bottled drinking, key, mineral, and iodized water. As well as their chemical content.